Assessment of p53 and ATM functionality in chronic lymphocytic leukemia by multiplex ligation-dependent probe amplification - te Raa, G D; Moerland, P D; Leeksma, A C; Derks, I A; Yigittop, H; Laddach, N; Loden-van Straaten, M; Navrkalova, V; Trbusek, M; Luijks, D M; Zenz, T; Skowronska, A; et al. (Cell death & disease, 2015)
The ATM-p53 DNA-damage response (DDR) pathway has a crucial role in chemoresistance in CLL, as indicated by the adverse prognostic impact of genetic aberrations of TP53 and ATM. Identifying and distinguishing TP53 and ATM functional defects has become relevant as epigenetic and posttranscriptional dysregulation of the ATM/p53 axis is increasingly being recognized as the underlying cause of chemoresistance. Also, specific treatments sensitizing TP53- or ATM-deficient CLL cells are emerging. We therefore developed a new ATM-p53 functional assay with the aim to (i) identify and (ii) distinguish abnormalities of TP53 versus ATM and (iii) enable the identification of additional defects in the ATM-p53 pathway. Reversed transcriptase multiplex ligation-dependent probe amplification (RT-MLPA) was used to measure ATM and/or p53-dependent genes at the RNA level following DNA damage using irradiation. Here, we showed that this assay is able to identify and distinguish three subgroups of CLL tumors (i.e., TP53-defective, ATM-defective and WT) and is also able to detect additional samples with a defective DDR, without molecular aberrations in TP53 and/or ATM. These findings make the ATM-p53 RT-MLPA functional assay a promising prognostic tool for predicting treatment responses in CLL.
Keywords: doxorubicin; poškození DNA; Gene Expression Regulation, Leukemic; mutace; vidarabin; protinádorové látky; DNA Damage; Vidarabine; Multiplex Polymerase Chain Reaction; epigeneze genetická; chemorezistence; Biological Assay; nádorový supresorový protein p53; regulace genové exprese u leukemie; polymerázová řetězová reakce s reverzní transkripcí; biotest; Gamma Rays; multiplexová polymerázová řetězová reakce; Ataxia Telangiectasia Mutated Proteins; Leukemia, Lymphocytic, Chronic, B-Cell; RNA nádorová; lidé; RNA, Neoplasm; Humans; Sensitivity and Specificity; senzitivita a specificita; Reverse Transcriptase Polymerase Chain Reaction; Drug Resistance, Neoplasm; Mutation; ATM protein; záření gama; chronická lymfatická leukemie; Doxorubicin; Tumor Suppressor Protein p53; Antineoplastic Agents; Epigenesis, Genetic